Strategy For Development Of Superior Sheep Breed In Increasing Income Of Rural Farmers - Dwi Priyanto; Ening Ariningsih; Mewa Ariani (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
The sheep farming system is still a side business in addition to farming in rural areas so it is not optimal. The breed factor is a major problem in the community with low body weight performance (small type). Indonesian Agency for Agricultural Research and Development (IAARD) (cq. Indonesian Research for Animal Production/IRIAP) has designed a superior breed of sheep with the name "Composite Sheep" which is directed at body weight performance and has a large type, namely through a cross breeding program of local sheep with imported sheep. The sheep that are formed have a greater body weight which are prepared as sheep export and are able to adapt to the tropical environment. In an effort to accelerate the existence of the population of superior sheep, source breeds management unit have carried out propagation in the laboratory and in breeders or farmer  livestock groups, so as to accelerate the management of superior breed, including efforts to maintain their purity. To accelerate population development, it is directed to collaboration with breeders/groups that are ready to be disseminated to the farmer. It is hoped that the spread of composite superior breeds can improve the business performance of farmers in rural areas, as well as be able to increase the farmer income in the community, with a higher selling value because they have a greater body weight than local sheep in rural areas.